Investment grants and firms' productivity: how effective is a grant booster shot? - Fernando Alexandre; Miguel Chaves; Miguel Portela (Small Business Economics, 2024)
This paper evaluates the impact of awarding a second investment grant to the same firm. We implement a Regression Discontinuity Design strategy using a rich firm-level administrative database, which allows us to link applications to grants and their scores to firms' performance. Our results show that while a single grant has a positive impact on firms' labour productivity, a second investment grant produces an even stronger effect. A more granular analysis suggests that only micro- and small-sized firms benefit from a single grant, whereas the overall effect of an investment grant booster shot is confirmed for the micro- and small-sized firms. No effects were found on total factor productivity for either the single or the second grant.
Keywords: D22; H25; L25; L52; 330; Industrial policy; Investment grants; Multiple grants; Productivity